Assessment of the information value of the Phoenix Sepsis Score after the first day of treatment of sepsis in children - P. I. Mironov; Yu. S. Aleksandrovich; A. V. Trembach; A. U. Lekmanov (Вестник анестезиологии и реаниматологии)
Introduction. Sepsis is a serious life-threatening disease, accompanied by high mortality and long-term decline in the quality of life of surviving patients. Recent recommendations from the US Society of Critical Care Medicine presented the Phoenix Sepsis Score as the optimal system for assessing organ dysfunction in children with sepsis.The objective of study was to compare the discriminatory ability of the Phoenix Sepsis Score, pSOFA and PELOD 2 scores after 24, 72 and 120 hours of intensive care.Materials and methods. The study design was retrospective, observational, and multicenter. 140 children met the inclusion and exclusion criteria, 29 (20.7%) patients died. The discriminatory power of the study scores was assessed based on ROC analysis.Results. The area under the ROC curve in the first 24 hours was comparable for the analyzed scores (within 0.600, the significance of the differences between the Phoenix Sepsis Score and pSOFA was 0.57, Phoenix Sepsis Score – PELOD 2 = 0.80, pSOFA – PELOD 2 = 0.74 ). On the third day of intensive therapy, the information value of the scores turned out to be good (Phoenix Sepsis Score– 0.704 ± 0.100, pSOFA – 0.748 ± 0.079, PELOD 2 – 0.810 ± 0.073), but they also did not differ statistically significantly from each other. On the fifth day of treatment, all scores showed excellent and comparable discrimination ability (AUG ROC about 0.900).Conclusions. The information ability of the Phoenix Sepsis Score, pSOFA and PELOD 2 in children with sepsis is comparable. The Phoenix Sepsis Score can be used to monitor the severity of organ dysfunction during intensive care of pediatric sepsis